Utilization of Hibiscus mutabilis. Linn. for Pulp and Paper - Negi, J. S.; Guha, S. R. D. (Indian Forester, 1978)
Hibiscus mutabilis was pulped by kraft process. High strength unbleached pulp can be produced from the debarked items in 40-50 per cent yield. Bark also produced pulp of good strength property but the yield was as low as 30%. Experimeat on Natural sulphite pulping process on debarked items produced pulp in 70% yield with light colour. The strength properties of the paper made from this pulp were comparable to kraft compared with normal bamboo kraft paper, except tearing strength all other properties were higher.